Study guides

☆☆

Q: What is equivalent to e equals 8b plus 12n?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b

7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4

11a+11b

10a - 10 b

Two equations, two unknownsFirst, multiply 3a + 2b = 70 by 4. This gives the equation 12a + 8b = 96. Next, subtract 4a + 8b = 70 from this equation. This result gives 8a = 26, which, solving for a, gives a = 3.25.Substitue the value of a into one of the original equations, which will give b = 7.125.Finally check your results by substituting the values of a and b into each equation.Answer:Given two equations 3a + 2b = 24 ------ (1) and 4a + 8b = 70 ------ (2) We have to solve this by using elimination method.Multiply the equation 3a + 2b = 24 by 4 on both the sides.We get 12a + 8b = 96 ---------- (3)Now, subtract the equation (2) from equation (3)12a + 8b = 96 ---------- (3)4a + 8b = 70 ---------- (2)--------------------------------(12a - 4a) + (8b - 8b) = (96 - 70)8a + 0 = 268a = 26a = 26/8a = 13/4 (Or) a = 3.25Substitute the value of a in the equation (2)4a + 8b = 70 ---------- (2)4(13/4) + 8b = 70.13 + 8b = 708b = 70 - 138b = 57b = 57/8 (Or) b = 7.125

Related questions

8b = -65 so b = -8.125

6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b

That's an equation in which b = -1

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4

8b

13b !

b^2 + 8b + 7 factors to (b + 7)(b + 1)

22b + 3

8b^2 -9b +1 8b^2 -8b -b +1 8b(b-1) - 1(b-1) (8b-1)(b-1)

11a+11b

5b2 = 8b therefore 5b =8 therefore b = 1.6

People also asked